The Influence of Work Motivation and Discipline on Employee Productivity PT. Aji Jaya Santosa - Astuti, Widia; Sunaryo, Sunaryo; Tanjung, Asridah Warni (Peneliti.net, 2024)
The purpose of this study was to determine the effect of workload and work discipline on employee performance at PT. AJI JAYA SANTOSA either partially or simultaneously. The method used is Quantitative Associative method. The population in this study are employees of PT. AJI JAYA SANTOSA. The sampling technique used is saturated sample method with a sample of 65 respondents. Methods of data analysis using simple linear regression test, multiple linear regression, correlation coefficient, coefficient of determination, partial t test and F test. The results of this study indicate that there is a positive and significant effect of workload on employee performance at PT. AJI JAYA SANTOSA this can be proven from the simple linear regression equation Y=3,465 + 2,277 X1. The correlation value is 0.423 (strong). The coefficient of determination is 46.2%. And the tcount value is tcount 3.362 > ttable 2.007. There is a positive and significant effect of work discipline on employee performance at PT. AJI JAYA SANTOSA this can be proven from the simple linear regression equation Y= 41.755 + 0.031 X2. The correlation value is 0.698 (strong). The coefficient of determination is 50.3%. And the tcount value is tcount 9.961 > ttable 2.007. Simultaneously there is a positive and significant effect of workload and work discipline on employee performance at PT. AJI JAYA SANTOSA this can be proven from the multiple linear regression equation Y = 36.254 + 0.280 X1 + 0.791 X2. The correlation value is 0.758 (strong). The coefficient of determination is 60%. And the Fcount value is Fcount 6.039 > Ftable 3.180.